Injured black men's perceptions of the recovery environment. (January 2022) - Bruce, Marta M.; Ulrich, Connie M.; Webster, Jessica; Richmond, Therese S.
Abstract: Background: Black men are disproportionately impacted by injuries in the United States. This disparity is glaring given that injury is one of the top ten causes of death. Injured Black men from disadvantaged neighborhoods experience higher injury mortality, years of life-expectancy loss, and psychological symptoms that persist after initial wounds have been treated. These injured men are typically transported to a hospital where they are medically stabilized and soon after are returned to the community. Black men are less likely to be discharged to comprehensive rehabilitation facilities, magnifying disparities in recovery from injury. While much research has examined individual characteristics that predict poor recovery from injury, fewer studies have focused on social and physical features of the environment and how they may impact the recovery of injury survivors. Purpose: The purpose of this study was to describe Black men's perceptions of how characteristics of their environment affect their recovery following serious injury. Methods: This was a secondary analysis of an existing data set consisting of semi-structured, qualitative interviews of 43 injured Black men in a northeastern city. The interviews were conducted three months following discharge from a large urban trauma center, and were audiotaped, transcribed verbatim, and de-identified. Thematic analysis consistent with the qualitative paradigm was used to identify themes. Results: Four themes were identified in injured men's narratives: challenges to recovery, feeling unsafe, efforts to increase safety, and resources for recovery. Conclusions: Our findings emphasize the importance of the role of community resources that can support injured men's recovery within their neighborhoods. Additional resources should be directed to survivors who return to disadvantaged communities after injury in order to minimize adverse emotional experiences that detract from recovery. Highlights: Injury recovery poses barriers for Black men returning to underserved neighborhoods. Varying resource availability presents challenges to recovery. Fear of reinjury and feeling unsafe leads to distress. Many relocate to increase safety or overcome physical and social barriers. Community resources are important in supporting injured men's recovery.